Postoperative Management of Eosinophilic Chronic Rhinosinusitis with Nasal Polyps: Impact of High-Dose Corticosteroid Nasal Spray - Ikeda,Katsuhisa (2019)
Abstract Introduction Eosinophilic chronic rhinosinusitis (ECRS) is characterized by an eosinophilic inflammation driven by Th2-type cytokines. Glucocorticosteroids are the most common first-line treatment for ECRS with nasal polyps. Objective We have evaluated the long-term treatment with double-dose intranasal corticosteroids in refractory ECRS nasal polyps resistant to the conventional dose and assessed the risk of adverse systemic effects Methods Sixteen subjects were enrolled in this study. All subjects had ECRS after endoscopic sinus surgery that resulted in recurrentmild andmoderate nasal polyps and were undergoing a postoperative follow-up application of mometasone furoate at a dose of 2 sprays (100 μg) in each nostril once a day (200 μg). All the patients were prescribed mometasone furoate, administered at a dose of 2 sprays (100 μg) in each nostril twice a day (400 μg) for 6 months. Results The average scores of the symptoms during the regular dose of intranasal steroid treatment were 5.2 ± 2.2, but 6 months after the high-dose application, they had significantly decreased to 2.5 ± 1.4 (p < 0.05). The polyp size showed an average score of 1.38 during the regular dose which was significantly reduced to 0.43 (p < 0.01) by the double dose. Glycated hemoglobin (HbA1c) showed normal ranges in all the patients tested. The cortisol plasma concentration was also normal. Conclusion Doubling the dose of the nasal topical spray mometasone furoate might be recommended for the treatment of recurrent nasal polyps in the postoperative follow-up of intractable ECRS.